INFLUENCE OF SECURITY CHALLENGES ON STUDENT ACADEMIC PERFORMANCE IN COLLEGE OF EDUCATION BILLIRI, GOMBE STATE, NIGERIA - MOHAMMED ABUBAKAR SABO; YAKUBU MUHAMMAD BELLO; MUHAMMAD AUWAL (International Studies Journal)
This study is carried out on the impact of insecurity challenges on students’ academic performance in College of Education Billiri, of Gombe State. The survey design and simple random sampling techniques were employed in this study. The population of the study are the 315 students of College of Education Billiri, of Gombe State, and a sample size of 152 students were randomly selected, a questionnaire (Impact of Security Challenges on Student Academic Performance in College of Education Billiri, of Gombe State) index (ISCSAP) was used as an instrument for data collection. Cronbach alpha correlation coefficient method is also used for the reliability. The researcher analyzed the responses by using mean statistics and standard deviation. Mean of 2.5 as acceptable, while below 2.5 will be rejected. The findings show law mean scores across all items indicates a widespread sense of insecurity and lack of confidence in the currents security measures, policies and personnel and the findings also indicate the security challenges in the college environment significantly affects aspects of student attendance and participation. The researchers conclude that the security challenges are not only disrupts the learning environment but also exacerbates stress and anxiety among students, further hindering their academic success. The major recommendations by the researchers are the management of the college are to invest in advanced and reliable security equipment, ensure the presence of adequately trained security personnel and implement comprehensive and effective security policies and procedures and establish counseling and psychological support services to help students manage stress and anxiety related to insecurity. Offer workshops and training sessions on coping mechanisms and resilience building.